2021
DOI: 10.1021/acsami.1c12590
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic Origin of Nonhysteretic Oxygen Capacity in Conventional Na-Excess Layered Oxides

Abstract: An intriguing redox chemistry via oxygen has emerged to achieve high-energy-density cathodes and has been intensively studied for practical use of anion-utilization oxides in A-ion batteries (A: Li or Na). However, in general, the oxygen redox disappears in the subsequent discharge with a large voltage hysteresis after the first charge process for A-excess layered oxides exhibiting anion redox. Unlike these hysteretic oxygen redox cathodes, the two Na-excess oxide models Na2IrO3 and Na2RuO3 unambiguously exhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 49 publications
1
11
0
Order By: Relevance
“…Although the OR reaction is identified as having a major role in compensating the charge imbalance induced by the Na‐extraction in all oxide cathodes, we propose that the chemical strength between M and O is a very important factor for making the OR reaction reversible and nonhysteretic during (de)sodiation, where M refers to Ni 4+ (3 d ‐ t 2 g 6 )O(2 p ), Mn 4+ (3 d ‐ t 2 g 3 )O(2 p ), and Ti 4+ (3 d ‐ t 2 g 0 )O(2 p ). [ 33 ] In the same manner, the strong chemical‐stiffness of TiO as a redox‐inactive species for Ti 4+ ‐NLMO leads to the largest decrease in the short OO(MnO 6 ) distance upon charging, whereas the MnO bond, featuring intermediate properties derived from the presence of the hybridized Mn 4+ ( t 2 g 3 )O(2 p ) band in low energy states, results in the mitigation of decreasing the short OO distance for Mn 4+ ‐NLMO. [ 34 ] Compared with the TiO and MnO bond‐containing oxides, the hybridized Ni( t 2 g 6 )O(2 p ) band responsible for the softness of the NiO bond in Ni 4+ ‐NLMO induces the smallest strain on the short OO distance in the MnO 6 octahedron.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the OR reaction is identified as having a major role in compensating the charge imbalance induced by the Na‐extraction in all oxide cathodes, we propose that the chemical strength between M and O is a very important factor for making the OR reaction reversible and nonhysteretic during (de)sodiation, where M refers to Ni 4+ (3 d ‐ t 2 g 6 )O(2 p ), Mn 4+ (3 d ‐ t 2 g 3 )O(2 p ), and Ti 4+ (3 d ‐ t 2 g 0 )O(2 p ). [ 33 ] In the same manner, the strong chemical‐stiffness of TiO as a redox‐inactive species for Ti 4+ ‐NLMO leads to the largest decrease in the short OO(MnO 6 ) distance upon charging, whereas the MnO bond, featuring intermediate properties derived from the presence of the hybridized Mn 4+ ( t 2 g 3 )O(2 p ) band in low energy states, results in the mitigation of decreasing the short OO distance for Mn 4+ ‐NLMO. [ 34 ] Compared with the TiO and MnO bond‐containing oxides, the hybridized Ni( t 2 g 6 )O(2 p ) band responsible for the softness of the NiO bond in Ni 4+ ‐NLMO induces the smallest strain on the short OO distance in the MnO 6 octahedron.…”
Section: Resultsmentioning
confidence: 99%
“…Although the OR reaction is identified as having a major role in compensating the charge imbalance induced by the Na-extraction in all oxide cathodes, we propose that the chemical strength between M and O is a very important factor for making the OR reaction reversible and nonhysteretic during (de)sodiation, where M refers to Ni 4+ (3d-t 2g 6)O(2p), Mn 4+ (3d-t 2g 3)O(2p), and Ti 4+ (3d-t 2g 0 )O(2p). [33] In the same manner, the strong chemical-stiffness of TiO as a redox-inactive species for Ti 4+ -NLMO leads to the largest decrease in the short OO(MnO 6 ) distance upon charging, whereas the MnO bond, featuring intermediate properties derived from the presence of the hybridized Mn 4+ (t 2g…”
Section: Ti 4+ -Induced "Potential-pillar" Effectmentioning
confidence: 93%
“…The closest material recently is Na[Li 0.2 Mn 0.8 ]O 2 , [107] where Li + instead of Na + enter the Mn layer. Besides, similar materials of other transition metals have been successfully synthesized such as Na 2 RuO 3 [108] and Na 2 IrO 3 , [109] which is attributed to the large difference in radius of Na + (1.02 Å) and Mn 4+ (0.53 Å). The structure of Na 2 MnO 3 may be stabilized by adding Ru or Ir into the Mn layer.…”
Section: High‐capacity Layered Naxmno2mentioning
confidence: 99%
“…Oxygen redox (OR) in oxide-based layered cathodes has been acknowledged to an intriguing mechanism that enables highenergy-density beyond that of the conventional cationic redox DOI: 10.1002/aenm.202303478 reaction rooted in transition metals (M) for sodium-ion batteries (SIBs). [1][2][3][4][5][6][7][8] The motivation in utilizing the OR for Nabased layered oxides was systematically derived from a well-known Li-excess Mn oxide (Li 2 MnO 3 ) that exhibits the anionic oxidation upon charging for lithium-ion batteries (LIBs), leading to the design of O3-type Na[Li 1/3 Mn 2/3 ]O 2 , operated by the pure oxygen oxidation above ≈4.0 V versus Na + /Na, delivering a high theoretical capacity of 285 mAh g −1 (if all Na ions are used) during desodiation. [9][10][11][12][13][14] This mechanism-driven computational design resulted in the successful synthesis of a Na intercalation cathode, and advanced experimental analyses clearly confirmed that the anionic reaction compensated for the charge imbalance induced by Na extraction from the host material.…”
Section: Introductionmentioning
confidence: 99%